Excited‐State Dynamics of Pentacene Derivatives with Stable Radical Substituents1. (30th April 2014) - Ito, Akitaka; Shimizu, Akihiro; Kishida, Noriaki; Kawanaka, Yusuke; Kosumi, Daisuke; Hashimoto, Hideki; Teki, Yoshio
Abstract The excited‐state dynamics of pentacene derivatives with stable radical substituents were evaluated in detail through transient absorption measurements. The derivatives showed ultrafast formation of triplet excited state(s) in the pentacene moiety from a photoexcited singlet state through the contributions of enhanced intersystem crossing and singlet fission. Detailed kinetic analyses for the transient absorption data were conducted to quantify the excited‐state characteristics of the derivatives.